Synthesis and biological evaluations of marine oxohexadecenoic acids: PPARα/γ dual agonism and anti-diabetic target gene effects - Sæther, Thomas; Paulsen, Steinar M; Tungen, Jørn Eivind; Vik, Anders; Aursnes, Marius; Holen, Torgeir; Hansen, Trond Vidar; Nebb, Hilde Irene (European Journal of Medicinal Chemistry, 2018)
Source at https://doi.org/10.1016/j.ejmech.2018.06.034. Obesity and associated disorders such as metabolic syndrome and type 2 diabetes (T2D) have reached epidemic proportions. Several natural products have been reported as Peroxisome Proliferator-Activated Receptor (PPAR) agonists, functioning as lead compounds towards developing new anti-diabetic drugs due to adverse side effects of existing PPAR drugs. We recently isolated and identified (7E)-9-oxohexadec-7-enoic acid (1) and (10E)-9-oxohexadec-10-enoic acid (2) from the marine algae Chaetoceros karianus. Herein we report the total synthesis, pharmacological characterization, and biological evaluations of these naturally occurring oxo-fatty acids (oFAs). The syntheses of 1 and 2 afforded sufficient material for extensive biological evaluations. Both oFAs show an appreciable dose-dependent activation of PPARα and -γ, with EC50 values in the micromolar range, and an ability to regulate important PPAR target genes in hepatocytes and adipocytes. Moreover, both 1 and 2 are able to drive adipogenesis when evaluated in the Simpson-Golabi-Behmel syndrome (SGBS) pre-adipocyte cell model, but with lowered expression of adipocyte markers and reduced lipid accumulation compared to the drug rosiglitazone. This seems to be caused by a transient upregulation of PPARγ and C/EBPα expression. Importantly, whole transcriptome analysis shows that both compounds induce anti-diabetic gene programs in adipocytes by upregulating insulin-sensitizing adipokines and repressing pro-inflammatory cytokines.